AZAN MAGAZINE AS A SPREADING MEDIA ISLAMIC KNOWLEDGE IN PATANI - Suraiya Chapakiya (Proceeding International Seminar of Islamic Studies, 2023)
Efforts to awaken humanity is not an easy endeavor. He requires seriousness and unified commitment at all levels and layers of society, especially those with the title of clergy and leaders. Scholars and leaders must be held accountable for the good and bad of something society and the ups and downs of a civilization. Rasulullah SAW said: